Analisis Kawih Gaya Ida Rosida Pada Lagu Reumis Beureum Dina Eurih - Tuti Triyani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
New Kawih Wanda is a kawih created by Mang Koko based on Mang Koko's understanding and ability to create a kawih with a new style at that time. In creating it because he wanted to present new works of Sundanese Karawitan, Mang Koko tried to process traditional and non-traditional musical material so that his work had breath. Baru (new color) from previously existing Sundanese karawitan. In this category, Mang Koko makes it happen through vocal and hand skills. A kawih interpreter who is quite famous in the Priangan area is Ida Rosida. One kawih interpreter who is quite popular among the people of West Java is Ida Rosida. She was born on 26 August 1954 and is the daughter of the founder of Sundanese kawih art in West Java, namely Hj Koko Koswara or known as Mang Koko. The aims of this research are: (1) to find out the Sundanese kawih singing technique in the song reumis beureum dina eurih style of Ida Rosida (2) to find out the form, meaning and structure of the presentation of the song reumis beureum dina eurih style of Ida Rosida. The method used in this research is qualitative with a descriptive analysis approach. The techniques used in this research are observation, interviews and documentation techniques. The main instrument in this research is the research itself using tools in the form of field notes and recording tools in the form of cellphones.